Violent conflict and international migration in Africa, 2005-2013 : empirical patterns and government challenges - Mongae, Mmabatho (My University, 2017)
This research report examines the governance and developmental challenges faced by countries that are major refugee destination countries. In doing so, I seek to examine the determinants of refugee outflows in Africa during the period of 2005 to 2013. I begin with the gravity model of refugee flows which helps identify and explain why certain countries tend to become major refugee destinations. The gravity model posits that refugee flows between two states is influenced by the distance and population size of both the destination and origin country. To this, I also add violent conflict which is expected to significantly affect refugee flows. In identifying major refugee destination nations, I also seek to understand which of these countries identify forced migration as a crucial governance and development challenge. The APRM text-mining analysis provides clarity on this. I use the statistical analysis to identify two countries that are popular refugee destination countries – Ethiopia and Kenya. I then present nested cases of trends of violent conflict and refugee flows. My central findings are that the presence of violent conflict in the source country strongly increases refugee outflows. I also find that distance plays a significant role in influencing migration decisions. The dynamics in the case studies reveal that African states are faced with different migration related challenges, and that the governance of migration is highly depended on the cooperation, will and commitment between the host and source countries.
A Research Report Submitted to the Faculty of Humanities by: In partial fulfillment of the requirements for obtaining the degree of Masters of Arts in International Relations
Keywords: International relations; Refugees--Government policy--Africa; Africa--Emigration and immigration